Numerical Investigation of Air-Coupled Generation of Lamb Waves in Isotropic Plates - Vilpisauskas, A.; Kazys, R. (Elektronika ir Elektrotechnika, 2014)
In the case of non-destructive testing and evaluation (NDT & NDE) of plate materials and structures ultrasonic Lamb waves are used. Very often air-coupled ultrasonic transducers are used for non-contact Lamb wave excitation and reception. This method has a very serious drawback: global insertion losses for an air-coupled system may be 120 dB–160 dB typically. In order to improve this NDT method a better understanding of Lamb wave excitation process is needed. A numerical investigation was performed in order to evaluate air-coupled Lamb wave excitation in an isotropic single layer plate. It is shown how Lamb wave normal displacement amplitude depends on an incidence angle and the distance between the plate and the transducer. DOI: http://dx.doi.org/10.5755/j01.eee.20.1.6162